GENDER DIVISION OF LABOUR AND POLYGAMY - Siti Aisyah (Al Qalam, 2009)
The Indonesian patriarchal culture and gender inequality is reflected in state policies, regulations and laws. As a pluralistic country comprising of different ethnic groups with specific cultures and traditions, Indonesia has four formal religions: Islam, Christianity, Hindu and Buddhism. Because of this, Indonesian law reflects cultural and religious diversity, including customary law or Adat law, the Marriage Law of 1974 as well as civil and criminal law. Two serious concerns of Marriage Law of 1974 are in relation to gender division of labour and polygamy which undermine Indonesian Muslim women. This paper discusses such an issue to allow women to get equaliry before the law and highlights its contribution to domestic violence.There are two contradictory stipulations with respect to the Marriage Law of 1974: equality in marriage and gender division of labour within marriage. On the one hand, Article 31 (1) and Article 3 3 clearly state that there is no difference between husband and wife with respect to their basic rights such as love; respect, or fidelity. On the other hand, both of these Articles are contradicted with other articles which differentiate between a husband's and wife's responsibilities. For example, Article 31 (3) and Article 34 stipulate a clear division between the roles of husbands and wives within marriage. This has become a reference point for Indonesian views in determining gender relations in marriage.Marriage Law of 1974 still which supports gender division of labour between wife and husband should be revised by providing a clear statement that these roles are conditional. This means that husbands can be domestic carers including taking care of children if they have no jobs, while wives can be finacial providers or the head of household if they are capable to do so. In this context, gender roles can be exchanged and are not strictly for a certain gender.